Associations between anthropometric indicators and refraction in school-age children during the post-COVID-19 era - Du, Wenzheng; Ding, Gang; Guo, Xiying; Abudukeyimu, Kadiya; Wang, Yanzhu; Wang, Lijun; Qi, Xiaoli; Ning, Yuxian; Hua, Ning; Song, Linlin; Li, Xue; Li, Jing; et al. (Frontiers in Public Health, 2023)
Purpose: To explore the associations between anthropometric indicators and refraction in school-aged children in the post-COVID-19 era. Methods: Data were collected from 25,644 children aged 7 to 12 years in 48 elementary schools in Tianjin. The comprehensive examination included height, weight, systolic blood pressure (SBP), diastolic blood pressure (DBP), refraction, and calculation of BMI, with a follow-up visit after six months. Myopia was defined as spherical equivalent refraction (SER) ≤−0.50 diopter (D). Bivariate correlation coefficients and multiple linear regression models were used to explore the cross-sectional and longitudinal associations between anthropometric indicators (height, weight, BMI, SBP and DBP) and refraction. Results: The mean changes in height, weight, BMI, SBP, DBP and SER of the participants were 4.03±2.18cm, 3.10±2.39kg, 0.45±1.16kg/㎡, 2.26±14.74mmHg, 2.18±11.79mmHg and-0.17±0.51D, respectively. Overall, height, weight, BMI, SBP and DBP were all correlated with SER (r=-0.324, r=-0.234, r=-0.121, r=-0.112, r=-0.066, both p < 0.001), and changes in height and weight were correlated with changes in SER (r=-0.034, -0.031, both p<0.001). Furthermore, multiple linear regression analysis revealed that the association of BMI, SBP and DBP with SER was significant in myopic children but not in non-myopic children. The association between changes in weight and changes in SER was only present in non-myopic children but not in myopic children. Conclusion: Height and weight were negatively correlated with SER in both cross-sectional analysis and longitudinal changes, indicating that children's height, weight and growth rate may be used as a reference indicator for myopia risk prediction and myopia progression monitoring.